1977
DOI: 10.1007/bf01964883
|View full text |Cite
|
Sign up to set email alerts
|

Histamine and acute haemorrhagic lesions in rat gastric mucosa: Prevention of stress ulcer formation by (+)-catechin, an inhibitor of specific histidine decarboxylase in vitro

Abstract: Acute haemorrhagic lesions in the oesophagus, stomach and duodenum ('stress ulcers') occur relatively often under clinical conditions and are always dangerous to the patient (lethality rate about 70%). Since conservative and surgical treatment are without significant success up to now, prevention by adaptation to stressors or by administration of drugs seems mandatory. An improved technique for producing acute gastric lesions in rats by immobilization and a new method for assessing this disease in the animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…There have been several reports concerning the anti-secretory and anti-ulcerogenic effect of catechins (Reimann et al 1977;Parmar & Ghosh 1981;Albinus et al 1983;Parmar & Hennings 1984;Jayaraj et al 1988). We investigated the effect of five catechins, ( + )-catechin, (-)-epicatechin, (-)-epicatechin gallate, (-)-epigallocatechin and (-)-epigallocatechin gallate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There have been several reports concerning the anti-secretory and anti-ulcerogenic effect of catechins (Reimann et al 1977;Parmar & Ghosh 1981;Albinus et al 1983;Parmar & Hennings 1984;Jayaraj et al 1988). We investigated the effect of five catechins, ( + )-catechin, (-)-epicatechin, (-)-epicatechin gallate, (-)-epigallocatechin and (-)-epigallocatechin gallate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reimann et al [55] showed that (+)-catechin (25 mg/kg), given intraperitoneally, prevented the formation of gastric lesions induced by immobilization in female rats. Nevertheless, orally administered (+)-catechin has not presented antiulcer activity in ethanol-induced gastric ulcers in rats [56] and could not be responsible for the detected antiulcerogenic activity of Terminalia fagifolia bark extracts.…”
Section: Discussionmentioning
confidence: 99%
“…8 In the gastrointestinal system, since Lorenz et al 9 reported, in 1975, the protective effect of catechin on stress ulcer formation, many studies have revealed protective effects of catechin in various models of gastric mucosal lesions. [10][11][12] Thus, we sought to investigate the mechanism of the inhibitory effect exerted by catechin on gastric mucosal lesions, in terms of changes in levels of gastrointestinal hormones that are fundamentally associated with peptic ulcer formation.…”
Section: Introductionmentioning
confidence: 99%